LRRC3B and its promoter hypomethylation status predicts response to anti-PD-1 based immunotherapy - Luo, Linfeng; Fu, Sha; Du, Wei; He, Li-na; Zhang, Xuanye; Wang, Yixing; Zhou, Yixin; Hong, Shaodong (Frontiers in Immunology, 2023)
The leucine rich repeat containing 3B (LRRC3B) gene is a tumor suppressor gene involved in the anti-tumor immune microenvironment. Expression of LRRC3B and DNA methylation at the LRRC3B promoter region may serve as a useful marker to predict response to anti-PD-1 therapy. Here, we evaluated the differential expression of LRRC3B in 33 cancer types in The Cancer Genome Atlas (TCGA) according to tumor stage, overall survival, and characteristics of the tumor microenvironment. LRRC3B expression associated with less tumor invasion, less severe tumor stage, and decreased metastasis. The inactivation of LRRC3B promoted the enrichment of immuneosuppressive cells, including myeloid-derived suppressor cells (MDSCs), cancer-associated fibroblasts (CAFs), M2 subtype of tumor-associated macrophages (M2-TAMs), M1 subtype of tumor-associated macrophages (M1-TAMs), and regulatory T (Treg) cells. We constructed a “silencing score” model base on LRRC3B promoter methylation to predict overall survival (OS) by multivariate Cox regression analysis. A high silencing score was significantly associated with immune inhibition, low expression of LRRC3B, poor patient survival, and activation of cancer-related pathways. Finally, the model was applied to predict anti-PD-1 therapy in non-small cell lung cancer (NSCLC) and breast cancer (BRCA). Our comprehensive analysis demonstrated the potential role of LRRC3B in the anti-tumor microenvironment, clinicopathological features of cancer, and disease prognosis. These findings suggest that LRRC3B methylation could be used as a powerful biomarker to predict immunotherapy responses in NSCLC and BRCA.